Upaya Pemulihan Kesehatan Penderita Tuberkulosis pada Masa Pandemi COVID-19 - Hendra Gunawan; Rahmat Rahmat; Iyep Dede Supriyatna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze efforts to restore the health of tuberculosis sufferers during the COVID-19 Pandemic in Cibiru Wetan Village, Cileunyi District, Bandung Regency. The method used is qualitative with a phenomenological approach through in-depth interview techniques. The study results a show that tuberculosis sufferers are still receiving treatment during the COVID-19 pandemic by implementing strict health protocols. In conclusion, efforts to restore the health of tuberculosis sufferers during the COVID-19 pandemic in Cibiru Wetan Village, Cileunyi District, Bandung Regency, are carried out through taking the medication regularly, checking themselves regularly at health care facilities and being accompanied by drug swallowing supervisors (PMO) from their family members. Keywords: COVID-19, Health Recovery, Tuberculosis Patients